Urinary tract infection in nephrotic syndrome in pediatric age group: a hospital based cross-sectional study - Mandal, Subinay; Samanta, Subhendu; Bakshi, Sabyasachi; Dash, Devidutta (International Journal of Contemporary Pediatrics, 2020)
Background: Nephrotic syndrome, characterized by the presence of heavy proteinuria, hypoalbuminemia, edema and hyperlipidemia, is a common renal disorder in pediatric population. Aim of this study were to find out the prevalence of Urinary Tract Infection (UTI) in nephrotic syndrome, bacterial etiologies and antibiotic sensitivity pattern. Methods: After matching the criteria, 82 cases, were taken for this prospective, single center, observational study. The diagnosis was confirmed by bacterial culture. This is an institution based cross-sectional descriptive observational study. All newly diagnosed and relapse cases of nephrotic syndrome based on inclusion exclusion criteria was included in this study. Respondent was either of the parents or caregiver of the study subjects. Analysis of all data was done by appropriate statistical software (SPSS-23). Results: Among 82 participants evaluated with nephrotic syndrome 29.3% participants had UTI, majority 66.7% were asymptomatic and 33.3% were symptomatic. Significant microscopic hematuria were found in 20.7% study subjects and significant pyuria were found in 58.54% study subjects. Majority of UTI caused by E.coli 33.3% followed by Klebsiella 25%, Proteus 16.7%, Staphylococcus aureus 12.5%, Citrobacter, Acinetobacter and mixed growth were found in 4.2% each. Mean serum cholesterol of group with UTI was 422.13±34.65 and group without UTI was 307.43±26.13. The variation amongst the two groups were found to be significant (p=0.0001). Conclusions: The children with nephrotic syndrome are frequently predisposed to UTI and in most cases it is asymptomatic, often undiagnosed. Higher serum cholesterol level may predispose the nephrotic child for UTI.